2021
DOI: 10.3389/fvets.2021.615730
|View full text |Cite
|
Sign up to set email alerts
|

Canine-Assisted Interventions in Hospitals: Best Practices for Maximizing Human and Canine Safety

Abstract: Canine-assisted interventions (CAI) are becoming more popular in hospital settings, representing a crucial intersection between animals, veterinary medicine, and society. However, standardized policies and procedures to minimize risk and maximize benefit to vulnerable humans and protect therapy dog welfare are lacking, posing a challenge to safe practice. Few intervention programs are evaluated to document efficacy compounding the potential risk. This paper presents a rationale for CAI in hospitals and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…These therapy dogs may participate in animal-assisted interventions, a broad category of tasks which can refer to either animal-assisted therapy-undertaken in conjunction with a health professional, working toward a specific goal-or animalassisted activity-undertaken in conjunction with a professional or volunteer in a more spontaneous setting (36). Although therapy dogs play important roles, this topic has been covered in depth elsewhere [e.g., (37,38)], and so the current paper focuses solely on assistance, protection, and detection dogs.…”
mentioning
confidence: 99%
“…These therapy dogs may participate in animal-assisted interventions, a broad category of tasks which can refer to either animal-assisted therapy-undertaken in conjunction with a health professional, working toward a specific goal-or animalassisted activity-undertaken in conjunction with a professional or volunteer in a more spontaneous setting (36). Although therapy dogs play important roles, this topic has been covered in depth elsewhere [e.g., (37,38)], and so the current paper focuses solely on assistance, protection, and detection dogs.…”
mentioning
confidence: 99%
“…Finally, regarding their relationships, handlers mentioned the influence of their own emotional state on their dog’s stress. It has been mentioned recently in a paper that handlers may suffer from compassion fatigue, which can compromise their own welfare but also the ability to lead AAI [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these claims are justified. For example, many studies have found that interacting with therapy dogs reduces stress and anxiety and increases positive emotional states in a variety of settings including hospitals, schools and nursing homes (15,16). In other cases, high public expectations about the healing power of pets are not matched by the results of empirical studies.…”
Section: Communicationmentioning
confidence: 99%